at-Tahdiy?t f? Ta?l?m al-A?w?t al-?Arabiyah li ad-D?ris?n al-Ind?n?siy?n wa Hul?liha - Isra Hayati Darman; Rani Ismil Hakim; Halimatus Sa`diyah; Ahmed Abdulkafi Almurib (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
?????? ?????: ???? ?????? ?? ??????? ?? ??? ??????? ??????? ??? ?????? ???????. ??? ????? ??? ?????? ???????? ?? ??????? ???????? ?? ??????? ???????? ?? ???? ????? ??? ?????? ???????? ?? ??????? ?????????. ???? ??? ??????? ??? ????? ???????? ???? ??????? ???????? ???????????? ?? ???? ??????? ??????? ??????? ?????? ???????? ?????????. ??????? ???????? ?? ??? ????? ?? ?????? ???????? ?????? ??????? ???????? ?? ??? ??????? ?????. ????? ????? ????? ??? ?? ?? ???????? ?? ???? ????? ????? ??????? ??: ???????? ?? ??? ???????? ???????? ????????? ?? ??? ????????? ????????? ?? ??? ????????. ???? ?? ?????? ??????? ??? ???????? ????: ????????? ???????? ???????? ??? ??????? ???????? ?????? ????????? ????????? ???????? ??????? ??????? ??????? ????????? ????????? ?? ????? ??????? ???????? ?????? ?????? ????? ??????? ??? ????? ???????? ???? ???????? ?? ?????? ????? ??????? ??????? ???????? ??? ????? ??? ????? ??????? ??? ????? ???????? ????????. ??????? ???????? : ????????? ??????? ????? ??????? Abstract: There are some errors in the pronunciation of Arabic sounds among university students. These errors are not limited to graduates of general or vocational high schools but also include some graduates of Islamic schools. This study aims to analyze the challenges faced by Indonesian learners in learning Arabic phonetics and identify solutions to address these challenges. The method used in this research is descriptive-analytical, involving the review of sources and references from books and scientific articles. The result indicate that the challenges in learning Arabic phonetics include phonetic-related issues, challenges from the learners’ side, and challenges from the teachers’ side. Proposed solutions to these challenges include intensive practice and focus on specific sounds, providing motivation to learners, utilizing digital tools and artificial intelligence for pronunciation training, designing phonetic learning materials based on contrastive studies, and ensuring that teachers understand the characteristics and features of Arabic sounds, and phonetic teaching be prioritized before vocabulary and grammar teaching. Keywords: Challenges, Solution, Phonetic teaching